INDOSAT PERDANA CARD PURCHASE DECISION PROCESS ON PRICE, PRODUCT QUALITY, AND PROMOTION IN MALANG CITY - Khotimah, Khusnul; Harjanti, Wulandari; Emmywati, Emmywati; Amrina, Amrina (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2021)
This study aims to determine the effect of partial and simultaneous prices, product quality and promotion on the Indosat's initial card purchase decision process in Malang City and find out the most influential variables on purchase decision process. This study uses a type of quantitative research with a population and sample of 100 Indosat consumer respondents in Malang City using multiple linear data analysis with the help of SPSS software. The results of the study show that prices, product, and promotion have simultaneously effect to Indosat's initial card purchase decision process in Malang city. And prices, product, and promotion have partial effect to Indosat's initial purchase decision process in Malang city. Dominant variable in influencing Indosat's initial card purchase decision process in Malang City is a promotion variable, with the influence value 38.4%.